EEWES: an energy-efficient wireless sensor network embed-ded system to be applied on industrial environments (2015)
Nowadays, the vast majority of information monitoring in industrial plants is still carried out by wired technologies, in which the installation and maintenance cost is high. However, in outdoor applications, such as those used in the oil and gas industry, the use of Wireless Sensor Networks (WSN) is increasing due to mobility, reliability, and low cost of the sensor nodes that make up the network. Moreover, this solution reduces the risks of workers in classified areas (regions with high probability of accidents occurrence) to the extent that the equipment maintenance is optimized.  This paper proposes the development of the EEWES, an energy efficient wireless sensor network embedded system, which can be applied on industrial environments. This development approach significantly reduces the energy consumption of the sensor nodes by using a method that alternates sleep periods of the transceiver/sensor set with data transmission/reception periods, which reduces the duty cycle while keeping the desirable parameters of the service quality (QoS). The results presented in this paper will be confirmed by field tests.